CONCEPT OF INTELLIGENT LOGISTIC FOR AUTOMOTIVE INDUSTRY - Hercko, Jozef; Micieta, Branislav; Botka, Milan; Zrnic, Nenad (Journal of Applied Engineering Science, 2016)
This paper describe concept of intelligent logistic for automotive industry created with value stream mapping. Automotive industry has been facing big impact of economic crisis in last years. European Commission prepared initiative to improve use of technology in automotive industry called Factories of the Future. This concept is using fourteen interrelated technology pillars to reach this goal. Application of this concept into automotive industry offer for company opportunity to be factory of the future with high level of competitiveness advantage.